Characterization of salmonella serovars by PCR–single-strand conformation polymorphism analysis - Nair, S.; Thong, Kwai Lin; Pang, T.; Altwegg, M. (American Society for Microbiology, 2002)
PCR-restriction fragment length polymorphism (PCR-RFLP) and PCR–single-strand conformation polymorphism (PCR-SSCP) analyses were carried out on the 1.6-kb groEL gene from 41 strains of 10 different Salmonella serovars. Three HaeIII RFLP profiles were recognized, but no discrimination between the serovars could be achieved by this technique. However, PCR-SSCP analysis of the groEL genes of various Salmonella serovars produced 14 SSCP profiles, indicating the potential of this technique to differentiate different Salmonella serovars (interserovar differentiation). Moreover, PCR-SSCP could differentiate strains within a subset of serovars (intraserovar discrimination), as three SSCP profiles were produced for the 11 Salmonella enterica serovar Enteritidis strains, and two SSCP profiles were generated for the 7 S. enterica serovar Infantis and five S. enterica serovar Newport strains. PCR-SSCP has the potential to complement classical typing methods such as serotyping and phage typing for the typing of Salmonella serovars due to its rapidity, simplicity, and typeability.